PENGARUH PROGRESSIVE MUSCLE RELAXATIOAN TERHADAP PENURUNAN PERILAKU KEKERASAN PADA PASIEN RESIKO PERILAKU KEKERASAN - Mareta Akhriansyah; Raden Surahmat; Nuriza Agustina; Amalia (Jurnal Kesehatan dan Pembangunan, 2026)
The risk of violent behavior includes behavior accompanied by destructive emotional responses that may result in both physical and psychological harm to others, oneself, and the environment. Management for patients at risk of violent behavior can be carried out through non-pharmacological interventions such as Progressive Muscle Relaxation (PMR). The purpose of this study was to determine the effect of PMR therapy on violent behavior in patients at risk of violent behavior at Yayasan Mitra Mulia. This study used a pre-experimental design with a one-group pretest-posttest approach. The sampling technique used in this study was purposive sampling, with a total sample of 37 respondents. The study measured anger behavior in people with mental disorders before PMR therapy was administered and then measured anger behavior again after the therapy was provided. The results showed that the median score for the ability to control anger behavior before therapy was 27.00 (poor), while the median score after therapy was 47.00 (good). Statistical analysis using the Wilcoxon test showed a difference in the total score of the ability to control anger behavior before and after PMR therapy (p-value = 0.000), indicating a significant effect. Based on the results of the study, it can be concluded that patients at risk of violent behavior who received anger behavior therapy experienced a reduction in violent behavior. It is expected that non-pharmacological treatment using PMR therapy can help reduce violent behavior in patients at risk of violent behavior.